Analysis of clinical characteristics of 2243 with positive anti‐gastric parietal cell antibody. Issue 7 (28th February 2020) - Guo, Yaping; Hao, Yingxia; Li, Xiaoyan; Liu, Xin; Liang, Ying; Song, Wenjie; Guo, Shuqin
Abstract: Background: To facilitate the early detection of chronic diseases, we analyzed the clinical characteristics of anti‐gastric parietal cell antibody (PCA)‐positive population, revealed the early characteristics of the population. Methods: According to the retrospective analysis, current situation investigation and comparative analysis of the clinical characteristics and medical history of the subjects, the comparison between the groups was performed. Result: (a) The positive rate of PCA detection in department of gastroenterology in our hospital was 35.80%. Among the individuals who underwent PCA, esophagogastroduodenoscopy (EGD) and pathological examination at the same time, 33.59% of the patients with PCA positive were diagnosed as atrophic gastritis by gastroscopy, which was much higher than 9.09% of the patients with PCA negative. (b) The incidence of gastroesophageal reflux, hypertension, ischemic heart disease (IHD) and cerebral ischemia in PCA‐positive population were 65.45%, 81.63%, 15.43%, and 31.61%, respectively, which were significantly higher than those in the control group. (c) The incidence rates of decreased red blood cells (RBC) and increased homocysteine (HCY) in laboratory‐related tests were 38.30% and 69.15%, respectively, which were much higher than those in control group. Conclusion: PCA has predictive value for a variety of chronic diseases and timely detection is of great significance.